Assessment of earthworm (Aporrectodea molleri)'s coelomic fluid-associated bacteria on different plant growth-promoting traits and maize germination and seedling growth. (July 2022) - Yakkou, Lamia; Houida, Sofia; Bilen, Serdar; Kaya, Leyla Okyay; Raouane, Mohammed; Amghar, Souad; El Harti, Abdellatif
Abstract: Earthworms together with plant growth-promoting bacteria (PGPB) can significantly increase the availability of nutrients and promote plant growth. However, earthworm's associated PGPB are poorly studied concerning their effect as biofertilizers to improve plant growth. In the current study, we aim to demonstrate that earthworm represents a reservoir and vector for PGPB through its coelomic fluid (CF), which is in permanent contact with the rhizosphere. To achieve this objective, 16 identified bacteria, previously, isolated from the (CF) of the earthworm Aporrectodea molleri, were tested for their potential to promote plant growth, in vivo and in vitro, by running 6 tests concerning 6 different PGP (Plant growth-promoting) characters, and co-inoculating maize seeds with potent bacteria. The results revealed that 87% of the CF's associated bacteria, have positive PGP traits. Out of the tested bacteria, 44% showed siderophores production, 25% and 37%, respectively, were positive for phosphate and potassium solubilizing in solid medium. Equally, 69% of the CF isolated bacteria showed phosphate solubilization, potassium solubilization, IAA production and nitrogen fixation abilities in liquid media. Moreover, 2 isolates (12%) inhibited the growth of the phytopathogenic fungus Fusarium oxysporum . Overall, the maize seeds treated with the CF's isolated bacteria LC68 ( Buttiauxella gaviniae ), LC27 ( Pantoea vagans ), LC12 ( Bacillus thuringiensis ) showed the better and, significantly, higher performance in germination speed and percentage, in addition to root and shoot length, and biomass. This work has highlighted that earthworm, in their coelomic fluid, harbour PGPB, which would stimulate plant growth and which could be involved in improving soil fertility. Highlights: Earthworms harbour bacteria with different Plant growth-promoting potentials. 87% of the earthworm's coelomic fluid bacteria have positive PGP traits. CF bacteria can inhibit the growth of the phytopathogenic fungus Fusarium oxysporum . Bacteria with significantly high PGP potency belong to Pseudomonas and Bacillus . CF's potent strains significantly promote growth of seedling maize in soil.